Faits d’actualité - H., J. (Assurances)

(untitled) (HEC Montréal, 1982)
Under the title "Faits d'actualité", the author reviews a certain number of subjects of current interest such as: Liability and indemnity; Mr. François Mitterrand's declaration regarding the nationalization of French insurance companies; Future relations of insurers and brokers; Insufficiency of insurance owing to increased cost of building and speculation; Effects of exchange rates on reinsurance results; America's new immobile society; Automobile insurance and the provincial government; Should repair cheques be made out in the names of both the insured and the garage owner; The remuneration of the insurance broker; Normal and abnormal growth of the brokerage office; The Insurance Bureau of Canada and government supervision.